Analysis of the Influence of Brand, Service, Image, Sales Promotion Staff, and Sales Discounts on Home Living Product Purchase Decisions at USUPSO Galaxy Mall Surabaya - Winarto Poernomo; Rheina Rizky Putri Indrianto; Arasy Alimudin (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: In this study aims to test and analyze Analysis of the Influence of Brand, Service, Image, Sales Promotion Staff, and Sales Discounts on Home Living Product Purchase Decisions at USUPSO Galaxy Mall Surabaya. Design/methodology/approach: In this study using quantitative research methods. This study uses a sample of 100 respondents from visitors and consumers who have made transactions or visited USUPSO Galaxy Mall Surabaya. This study uses Non Probability Sampling with Accidental Sampling technique, which is a sampling technique based on chance, mean anyone who happens to be met can be used as a sample, if the person who happens to be met is suitable as a data source. In data collection, as well as testing using the help of data analysis, namely the SPSS program. Findings: The results of this study indicate that the brand, service, image, sales promotion staff and sales discounts partially positive effect. Simultaneously brand, service, image, sales promotion staff and discounts also have a significant effect on purchasing decisions. Paper type: Research paper